Atypical Appendicitis In Celiac Disease - Stephanie Aurelia Santoso; Irene Aurelia Santoso (International Journal of Health Engineering and Technology, 2026)
Celiac Disease (CD) is an autoimmune disorder affecting the small intestine due to gluten ingestion and often manifests atypically. While appendicitis in children typically presents with standard symptoms, younger patients or those with comorbidities like CD may exhibit nonspecific signs that delay diagnosis. We describe a case involving a 3-year-old girl who presented with right lower abdominal pain alongside a low Pediatric Appendicitis Score (PAS), positive tTG-IgA serology, and increased fecal calprotectin levels. Despite inconclusive abdominal ultrasound results, diagnostic laparoscopy confirmed an inflamed appendix containing fecaloma. Histopathological analysis verified acute appendicitis. Post-appendectomy care led to the patient’s improvement and further plans for evaluation and education regarding a gluten-free diet. This case emphasizes the diagnostic difficulties associated with atypical appendicitis in CD patients and highlights the necessity of multidisciplinary assessments as well as the effectiveness of diagnostic laparoscopy when faced with ambiguous clinical presentations. A thorough approach can mitigate delays in diagnosis and ensure optimal patient management.